Roles of NOTES and LESS in management of small renal masses. (December 2016) - Kim, Dae Keun; Yoon, Young Eun; Han, Woong Kyu; Rha, Koon Ho
Abstract: Introduction: Over the last 2 decades, open surgery has been largely displaced by laparoscopic surgery for the treatment of renal masses. Recently, minimally invasive surgical techniques, such as laparoendoscopic single-site surgery (LESS) and natural orifice transluminal endoscopic surgery (NOTES), have been developed for such purpose. Methods: In the present literature review, the current status of treatment for small renal masses was investigated. The advantages and disadvantages of LESS and NOTES are presented to confirm the feasibility and reproducibility of these techniques. Results: LESS significantly reduces pain and offers excellent cosmetic outcomes with comparable oncological and perioperative results, and NOTES offers the potential for surgery by various approach without any transcutaneous abdominal incision in management of small renal masses. Conclusion: When the technical limitations are overcome, clinical application of LESS and NOTES is expected to increase. Further prospective and comparative studies are needed to clarify the application of these new techniques. Highlights: LESS and NOTES are innovative techniques for treatment of small renal masses. Further study is needed to clarify the advantages.